2008
DOI: 10.1007/s10552-008-9188-8
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to vinyl chloride and risk of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common form of cancer that arises from hepatocytes and whose risk may be affected by several known factors, including viruses, alcohol, cigarette smoking, and several genetic conditions. Liver angiosarcoma is a rare cancer that develops from endothelial cells and whose most relevant known risk factor is occupational exposure to vinyl chloride (VC). Since occupational exposure to high levels of VC may still occur, we reviewed the epidemiological and experimental evidence supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…induce specific gene mutations in the liver [105][106][107][108][109][110][111][112][113][114][115][116][117] . Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…induce specific gene mutations in the liver [105][106][107][108][109][110][111][112][113][114][115][116][117] . Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…The trial elicited original studies from consultants to the public prosecutors, who provided part of the available evidence on the association between VC and HCC [Pirastu et al, 2003;Mastrangelo et al, 2004]; additional studies from independent researchers were consistent with this finding, which was confirmed by the last IARC assessment. Consultants of the VC industry issued 4 reviews of epidemiological studies (out of 6 published in English language since the beginning of the trial) [McLaughlin and Lipworth, 1999;Bosetti et al, 2003;Dragani and Zocchetti, 2008;Sherman, 2009]. The first reviews amplified doubts and limitations in the available literature, and supported the judges' decision on the presence of uncertainties about the association between VC and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…No available risk assessment suggests that an ambient level of VCM of 0.01 µg/m 3 presents a risk of harm based on exposures over an average lifetime. In humans, the level of exposure to VCM must be > 7,531 ppm-years to develop ASL [4] 1 . Available information suggests that exposure to VCM must be 10-fold higher to develop HCC, far exceeding actual exposures.…”
mentioning
confidence: 99%
“…Available information suggests that exposure to VCM must be 10-fold higher to develop HCC, far exceeding actual exposures. The evidence of risk of HCC from VCM exposure is based on a few and overlapping data [4-6] 2, 3 .…”
mentioning
confidence: 99%